COMPREHENSIVE APPROACH TO PRE- UNIVERSITY EDUCATION - Natalya G. Shilina; Elena V. Taptygina (Высшее образование в России)
The experience of the Faculty of preBuniversity and continuing education of the Krasnoyarsk State Medical University named after Prof. V.F. VoynoBYasenetsky aimed to attract careerBoriented applicants who have got a preBuniversity training including learning of special for medical school subject courses. The article presents a comprehensive approach that includes new forms of organization of preBuniversity educational programs for applicant’s preparation, which include fullBtime courses and distance learning cycles; career guidance activities and attracting for applicants to participate in the competition of scientific works. One of the new forms of preBuniversity training is a special medical practice for applicants. For the first time it was organized in 2013.